An Innovative Electromagnetic Integration Method for LCL Filters in Grid-Connected Inverters - Wei, Wei; Ma, Junxian; Zhao, Jiaqi; Hai, Yaning; Zhou, Zongchuan; Chen, Na (2023 2nd International Conference on Clean Energy Storage and Power Engineering (CESPE), 2023)
In the field of current harmonics filtering for grid-tied inverters, LCL filters are considered more feasible than L (LC) filters due to their superior harmonic depression capability, reduced filter size, and weight. However, with the widespread adoption of wide bandgap semiconductors, discrete LCL filters hinder the development of compact and efficient inverter systems. To address this issue, we propose a novel electromagnetically integrated method that utilizes flexible multilayer foil (FMLF) technique for LCL filters to enhance effective volume. The feasibility of this approach is demonstrated through investigation of a prototype employing FMLF-winding. In our work, both inductors and capacitors of the LCL filter are simultaneously integrated on one EE-type core, effectively utilizing the core's window area and significantly improving system power density. Simulation and experimental results validate the effectiveness and superiority of our proposed method.